2016
DOI: 10.1519/jsc.0000000000001371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sodium Chloride Tablets–Induced, Sodium Chloride Solution–Induced, and Glycerol-Induced Hyperhydration on Fluid Balance Responses in Healthy Men

Abstract: Savoie, FA, Asselin, A, and Goulet, EDB. Comparison of sodium chloride tablets-induced, sodium chloride solution-induced, and glycerol-induced hyperhydration on fluid balance responses in healthy men. J Strength Cond Res 30(10): 2880-2891, 2016-Sodium chloride solution-induced hyperhydration (NaCl-SolIH) is a powerful strategy to increase body water before exercise. However, NaCl-SolIH is associated with an unpleasant salty taste, potentially dissuading some athletes from using it and coaches from recommending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 40 publications
1
20
2
Order By: Relevance
“…We believe that during the TC digestion process some bioactive peptide with haematopoietic properties can be obtained. In addition, we believe that the high levels of sodium and chloride present in TC could increase fluid retention and generate hypervolaemia, thereby decreasing haematocrit [ 53 , 54 ]. Further research is needed to explain the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that during the TC digestion process some bioactive peptide with haematopoietic properties can be obtained. In addition, we believe that the high levels of sodium and chloride present in TC could increase fluid retention and generate hypervolaemia, thereby decreasing haematocrit [ 53 , 54 ]. Further research is needed to explain the results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The taste of salt drinks is often not pleasant and salt tablets as an alternative has been investigated with regards to fluid retention capacity. Savoie, et al (834) reported that a salt solution provided better fluid retention than tablets with equal concentrations of sodium, probably due to the time it takes the tablets to dissolve in the stomach. Sodium supplementation may be required during prolonged exercise to attenuate hyponatremia when large volumes of fluid are consumed.…”
Section: Sodiummentioning
confidence: 99%
“…204 Little evidence supports this practice for either hyperhydration before activity 205 or fluid retention during activity. 204 Furthermore, adverse events associated with this practice during activity are unknown.…”
mentioning
confidence: 99%